Geographic Information for Disaster Management in Nigeria: Case Study of the Mud-beach Coast of Southwestern Nigeria - Fasona, Mayowa; Akinlabi Akintuyi, Ademola Omojola, Alabi Soneye; Abbas, Innocent (Unilag Journal of Humanities, 2019)
This paper demonstrates the importance of geographic information in disaster management. It examines the state of disaster management in Nigeria and presents a local area case study of the use of geographic information to establish the vulnerability to composite environmental threat and hazard of 605 communities around the mud-beach coast of southwestern Nigeria. Environmental threat and hazard factors interpreted from remote sensing imageries were integrated within geographic information systems with data that characterized the communities. The integrated data was further analyzed for indices of exposure (stressors which define damage potentials) and management (likely coping ability which defines severity) for each community. Vulnerability index for each community was evaluated by comparing the difference between the degree of exposure and management. In terms of exposure, the results suggest that 18 communities fall under high exposure, 129 under medium exposure and 458 under low exposure categories. For management, 41 communities fall under the high management-low severity, 131 under average management-average severity and 433 under the low management-high severity categories. In all, 70 communities, most of which are first-line settlements, are highly vulnerability to composite environmental hazard. 80% of the highly vulnerable communities are found around degraded ecosystems including permanently inundated lands and areas where active devegetation is being experienced, which confirms the connection between creeping environmental change process and vulnerability to disasters especially at local levels.